2009
DOI: 10.1073/pnas.0911503106
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mutant huntingtin in mouse brain astrocytes causes age-dependent neurological symptoms

Abstract: Huntington disease (HD) is an inherited neurological disorder caused by a polyglutamine expansion in the protein huntingtin and is characterized by selective neurodegeneration that preferentially occurs in striatal medium spiny neurons. Because the medium spiny neurons are innervated abundantly by glutamatergic axons from cortical neurons, the preferential degeneration in the striatal neurons supports the glutamate excitotoxicity theory for HD pathogenesis. Thus, glutamate uptake by glia may be particularly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
265
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(271 citation statements)
references
References 37 publications
5
265
0
1
Order By: Relevance
“…Consistent with prior research, we have provided direct evidence that mutant Htt-552 in glial cells reduced the expression of GLT-1 but not of GLAST and decreased glutamate uptake in astrocytes, which was mainly caused by decreased expression of GLT-1. Because there are Sp1-binding sites in the promoter of GLT-1 and the transcription of GLT-1 is Sp1-dependent [24,25] , previous reports of mutant Htt binding more Sp1 and reducing Sp1-mediated GLT-1 expression in astrocytes may explain this www.chinaphar.com Chen LL et al Acta Pharmacologica Sinica npg phenomenon [10] .…”
Section: Recovery Of Glt-1 Expression and Function By Rapamycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior research, we have provided direct evidence that mutant Htt-552 in glial cells reduced the expression of GLT-1 but not of GLAST and decreased glutamate uptake in astrocytes, which was mainly caused by decreased expression of GLT-1. Because there are Sp1-binding sites in the promoter of GLT-1 and the transcription of GLT-1 is Sp1-dependent [24,25] , previous reports of mutant Htt binding more Sp1 and reducing Sp1-mediated GLT-1 expression in astrocytes may explain this www.chinaphar.com Chen LL et al Acta Pharmacologica Sinica npg phenomenon [10] .…”
Section: Recovery Of Glt-1 Expression and Function By Rapamycinmentioning
confidence: 99%
“…The transcription of GLT-1 was Sp1-dependent, and it had been reported that mutant Htt bound more Sp1 and reduced Sp1-mediated GLT-1 expression in astrocytes. This could lead to defective glial glutamate uptake and increased neuronal excitotoxicity [10] . Therefore, we want to know if the expression of GLT-1 would return to a normal level after mutant Htt had been cleared.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain of patients suffering from neurodegenerative diseases [138][139][140] and in animal models of these disorders [141][142][143][144], signs of massive neuroinflammation are detected. Importantly, the phenotype of both astrocytes and microglia changes in ageing.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…11,12 Mutant HTT is expressed in glial cells, 13,14 and transgenic mice overexpressing mutant HTT in astrocytes show age-dependent neurological symptoms. 15,16 Additionally, primary astrocytes overexpressing full-length human mutant HTT show reduced mRNA levels of cholesterol biosynthetic genes, along with impaired cellular production and secretion of apoE. 8 Here we employed molecular and cellular tools to test the impact of cholesterol perturbation between astrocytes and neurons in HD.…”
mentioning
confidence: 99%